Bhutan : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Bhutan. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses the recent economic developments, outlook, and risks for Bhutan. Following a slowdown in activity in the wake of the rupee shortage, economic growth has picked up more recently. From an average of about 8 percent during the Ninth and Tenth Five-Year Plans spanning fiscal years (FYs) 2003/04-2012/13, real GDP growth fell below 4 percent in FY2012/13 and FY2013/14. Bhutan's medium-term outlook remains favorable. Commissioning of new hydropower generation projects will boost output, exports, and fiscal revenues. However, domestic risks stem from the need to manage high debt and potentially volatile hydropower-related inflows, which may fuel rapid credit growth and lead to renewed external pressure.